Controlled ovarian hyperstimulation parameters are not associated with de novo chromosomal abnormality rates and clinical pregnancy outcomes in preimplantation genetic testing - Liu, Yanli; Shen, Junhan; Zhang, Yuchao; Peng, Rui; Zhao, Junliang; Zhou, Pengfei; Yang, Rujing; Guan, Yichun (Frontiers in Endocrinology, 2023)
Objective: This study aimed to determine whether controlled ovarian hyperstimulation (COH) parameters influence the incidence of de novo chromosomal abnormalities (> 4 Mb) in blastocysts and, thus, clinical pregnancy outcomes in preimplantation genetic testing (PGT). Methods: Couples who underwent preimplantation genetic testing for structural chromosome rearrangements (PGT-SR) and monogenic disorders (PGT-M) were included in this study. The relationships of maternal age, paternal age, stimulation protocol, exogenous gonadotropin dosage, duration of stimulation, number of oocytes retrieved and estradiol (E2) levels on human chorionic gonadotropin (hCG) trigger day with the incidence of de novo chromosomal abnormalities were assessed. Blastocysts were biopsied, and nuclear DNA was sequenced using next-generation sequencing (NGS). Clinical pregnancy outcomes after single euploid blastocyst transfers under different COH parameters were assessed. Results: A total of 1,710 and 190 blastocysts were biopsied for PGT-SR and PGT-M, respectively. The rate of de novo chromosomal abnormalities was found to increase with maternal age (p < 0.001) and paternal age (p = 0.019) in the PGT-SR group. No significant differences in the incidence of de novo chromosomal abnormalities were seen for different maternal or paternal age groups between the PGT-SR and PGT-M groups (p > 0.05). Stratification analysis by gonadotropin dosage, stimulation protocol, duration of stimulation, number of retrieved oocytes and E2 levels on hCG trigger day revealed that de novo chromosomal abnormalities and clinical pregnancy outcomes were not correlated with COH parameters after adjusting for various confounding factors. Conclusion: The rate of de novo chromosomal abnormalities was found to increase with maternal or paternal age. COH parameters were found to not influence the incidence of de novo chromosomal abnormalities or clinical pregnancy outcomes.